Optimalisasi Pengembangan Desa Sebidai Menuju Desa Mandiri Melalui Program Kuliah Kerja Nyata (KKN) - Nurjannatul Hasanah; Rahmi Nur Islami; Ahmad Fuad Hasim (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
One of the mandatory programs for students of Borneo Tarakan University is the Real Work Lecture (KKN) by combining students from various departments into one group placed in a village to carry out community service. Group 19 was placed in Sebidai Village, Tana Tidung with the aim of